2016
DOI: 10.1093/rheumatology/kew356
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in health-related quality of life and functional ability in patients with gout

Abstract: Objective. To compare the health-related quality of life (HRQOL) and the functional ability by race in patients with gout.Methods. In a 9-month prospective cohort multicentre study, patients with gout self-reported race, dichotomized as Caucasian or African American (others excluded). We calculated HRQOL/function scores adjusted for age, study site and college education for Short Form-36 (SF-36; generic HRQOL), Gout Impact Scale (GIS; disease-specific HRQOL) and HAQ-disability index (HAQ-DI; functional ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Existing studies have documented that demographic and clinical variables have an impact on functional disability and HRQoL in individuals with gout [ 10 , 11 , 33 ]. Similar to the results of Chandratre et al, the data in the present study showed that DM has a substantial impact on HAQ-DI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have documented that demographic and clinical variables have an impact on functional disability and HRQoL in individuals with gout [ 10 , 11 , 33 ]. Similar to the results of Chandratre et al, the data in the present study showed that DM has a substantial impact on HAQ-DI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that gout individuals had impaired overall HRQoL compared with general population [ 8 , 9 ]. It has been reported that socioeconomic status and disease-related characteristics may have an impact on functional disability and HRQoL in subjects with gout [ 8 , 10 , 11 ]. Current evidence estimated that gout patients affected by severe pain, tophi, polyarticular disease, a great number of attacks, and more number of involved joints frequently had functional disability and worse HRQoL [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gout is a painful, inflammatory form of arthritis, caused by abnormal metabolism of purines and the resulting accumulation of uric acid crystals within the joints and other tissues [ 1 , 2 ]. Estimates indicate that 1 to 3% of the Chinese population has gout [ 3 ], with the incidence rate gradually increasing [ 4 , 5 ]. Individuals with gout experience severe gout flares, chronic recurrent pain, and joint swelling, resulting in a reduction in their quality of life (QoL) [ 6 , 7 ], which is poorer in individuals with gout than in physically and mentally healthy persons [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…n = 400 in the fully adjusted model testing the association between low K-Wood-MAS-4 adherence and decline in PCS). Race differences in adherence [ 36 ] and HRQOL [ 37 ] warrant further research with larger subgroup samples.…”
Section: Discussionmentioning
confidence: 99%